Six decades of radar and seismic research in Antarctica - S. V. Popov (Лëд и снег, 2021)
Antarctica was discovered by the First Russian Antarctic expedition in 1820. Subsequent studies were mainly descriptive in nature, and measurements were few in number. Only from the end of the 19th century systematic scientific observations were started in Antarctica. The first stage of studying the continent was completed in the middle of the 20th century, when the coastline was completely mapped and inland studies were carried on. The First International Geophysical Year (1957–1958) marked the beginning of systematic geophysical researches in Antarctica. Russia (USSR) took an active part in the work, opening Mirny and Pionerskaya stations in 1956. At the same time, seismic sounding, first conducted by the R. Byrd's expedition in 1933–1935, began to be carried out in Antarctica. In the first two decades after the International Geophysical Year, international scientific communities carried out the first comprehensive multidisciplinary research; a network of permanent year-round scientific stations was created, and a new method of radar sounding was introduced into the practice of work. The results of this stage are presented in the two-volume Atlas of Antarctica, published in the USSR. In the 1970s and 90s, most of the continent was covered by complex airborne geophysical surveys. The huge amount of accumulated data has been combined for generalization them into a single database within the framework of the International Bedmap project. Recent studies are mainly focused in unexplored areas of Antarctica, which by now are actually absent. Further accumulation of data promoted the two subsequent generations of the Bedmap project - Bedmap2 and Bedmap3. The use of GPR methods since the late 1990s has allowed us to study the structure of the snow-firn thickness at a new scientific and technical level, as well as to perform important engineering surveys aimed at ensuring the safety of transport operations in Antarctica. Currently, Russian research is focused on the study of the subglacial Lake Vostok and airborne geophysical works in the sector of 60°–100° E.